TP53 Co-Mutations in Advanced EGFR-Mutated Non–Small Cell Lung Cancer: Prognosis and Therapeutic Strategy for Cancer Therapy - Liu, Surui; Yu, Jin; Zhang, Hui; Liu, Jie (Frontiers in Oncology, 2022)
Lung cancer is the leading cause of cancer-related deaths worldwide. EGFR mutations are the most prevalent molecular subtype in patients with non-small cell lung cancer (NSCLC) in Asia. EGFR-TKIs are currently a standard first-line therapy for advanced EGFR-mutated NSCLC patients. However, 20-30% of this subset of patients shows primary resistance to EGFR-TKIs. Patients with comutations of EGFR and several other genes have poor response to EGFR-TKIs, whereas the prognostic and predictive significance of EGFR/TP53 comutation in NSCLC patients remains controversial. Meanwhile, little is known how to choose optimal therapeutic strategy for this subset of patients. At present, no drugs targeting TP53 mutations are available on the market, and some p53 protein activators are in the early stage of clinical trials. Combination of EGFR-TKIs with antiangiogenic agents or chemotherapy or other agents might be more appropriate strategy to tackle the problem. In this review, we describe the prognostic and predictive value of EGFR/TP53 comutation in NSCLC patients, investigate the mechanisms of this comutation affecting the response to EGFR-TKIs, and further explore optimal regimens effectively to prolong the survival time the NSCLC patients harboring this comutation.